2010
DOI: 10.1097/rlu.0b013e3181e05d79
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Transporter Expression of an Esophageal Gastrointestinal Tumor Detected by F-18 FDG PET/CT

Abstract: A 74-year-old woman had dysphagia and underwent esophagogastroduodenoscopy. A giant submucosal tumor was seen from the middle to the lower esophagus. Fluorine-18 fluorodeoxyglucose positron emission tomography/computed tomography (F-18 FDG-PET/CT) was performed and F-18 FDG was found to accumulate in the submucosal tumor. The maximum standardized uptake value of the early phase was 4.93 and that of the delayed phase was 6.48. Gastrointestinal stromal tumor (GIST) was confirmed by both fine needle aspiration un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Elevated glucose uptake and preferential metabolism by aerobic glycolysis was first described by Otto Warburg in the early 1900s 11 . This property of increased glucose uptake in cancer cells forms the basis of [ 18 F] fluoro-2-deoxyglucose-positron emission tomography (FDG-PET) used in the diagnosis and prognostic monitoring of cancer 12 , however this phenomenon has not yet been capitalized upon for therapy. Various agents such as genistein, fasentin, STF-31, 2-deoxyglucose and 3 bromopyruvate are being investigated for their ability to target glucose metabolism 1317 …”
Section: Introductionmentioning
confidence: 99%
“…Elevated glucose uptake and preferential metabolism by aerobic glycolysis was first described by Otto Warburg in the early 1900s 11 . This property of increased glucose uptake in cancer cells forms the basis of [ 18 F] fluoro-2-deoxyglucose-positron emission tomography (FDG-PET) used in the diagnosis and prognostic monitoring of cancer 12 , however this phenomenon has not yet been capitalized upon for therapy. Various agents such as genistein, fasentin, STF-31, 2-deoxyglucose and 3 bromopyruvate are being investigated for their ability to target glucose metabolism 1317 …”
Section: Introductionmentioning
confidence: 99%
“…The reason why some leiomyoma cells had strong expression of Glut-3 is Glut-4 is the major insulin regulated glucose transporter, mainly in muscle and adipose tissue. Kaida et al [7] reported that FDG-PET positive GIST had strong expression of Glut-4 concomitant with weak expression of Glut-1 and no expression of Glut3. Tarn et al [22] also reported that GIST have more Glut-4 expression than Glut-1 expression and that the expression of Glut-4 is decreased Expression of Glut-4 is homogeneous by the administration of Imatinib.…”
Section: Discussionmentioning
confidence: 98%
“…Several Glut isoforms have been identified and associated with FDG trapping in malignant tumors [12][13][14]. Of them, Glut-1, 2, 3 and 4 had been reported to play important roles in FDG accumulation [7,15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was also shown that GLUT4 inhibition abrogates cell proliferation and chemoresistance in vitro in MM, chronic lymphocytic leukemia (CLL), solid tumor lines and in vivo in a xenograft model of MM [910, 1819]. Roles for GLUT4 have also been suggested in human gastrointestinal tumors that exhibit enhanced PM localization of GLUT4 and weak expression of GLUT1 [20] and in breast cancers [21]. In sum, these observations suggest GLUT4 serves a unique role in both solid and liquid cancers.…”
Section: Introductionmentioning
confidence: 99%